Rice stable carbon and nitrogen isotope values as potential indicators of watering and manuring regimes - Wu, Rubi; Belfield, Eric J.; Dong, Yu; Feng, Shangzong; Fu, Xiangdong; Harberd, Nicholas P.; Yang, Fan; Charles, Michael; Bogaard, Amy (Frontiers in Environmental Archaeology, 2025)
Rice (Oryza sativa L.) is an important cereal crop across East, South and Southeast Asia, from prehistory to today, and grows in a range of ecological conditions, from rainfed upland to deep water. Previous research on early rice in the Lower Yangtze River basin (LYRB) suggested shifts back and forth over time between wet and dry field conditions, and some application of animal dung and/or human feces as fertilizer. In this study, stable carbon and nitrogen isotope analysis was conducted on grains from rice of heritage landraces and modern varieties grown in a glasshouse pot experiment with three watering levels and two manuring levels, and from recent rice fields in China and South Korea including paddy and dry conditions, and with variable manuring histories. The pot experiment results indicate that there is a negative correlation between the δ13C values and watering levels in one heritage accession and three modern accessions; in the remaining two heritage accessions and one modern accession, a similar trend in δ13C values is observed between watering levels. The rice field results show that, similarly, the δ13C values of rice from paddy fields were significantly lower than those from dry fields. The results from the pot experiment also indicate that both watering and manuring tend to increase the δ15N values of rice grains, while the field samples show that intensive manuring in initial growing seasons does not have a consistent effect on rice δ15N values. Overall, stable carbon and nitrogen isotope values of rice grains appear to be useful indicators of water status, with potential in combination to disentangle watering and manuring practices.